Implementation of Halaqoh and Musyafahah Methods in Memorizing the Qur'an at Hidayatul Mubtadiin Islamic Boarding School - Muhammad Riyadh; Imam Syafe'i; Eka Prastiawati (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the implementation of the halaqoh and musyafahah methods in memorizing the Qur'an and their impact on the quality of students' memorization at Pondok Pesantren Hidayatul Mubtadiin, Tulang Bawang Barat. This research employs a qualitative approach with a case study design. The research subjects consisted of 5 tahfidz instructors and 27 students in the tahfidz program. Data collection techniques included participatory observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion. The results showed that the halaqoh method is implemented through a circular group system which effectively improves memorization fluency and a sense of togetherness. The musyafahah method is implemented through direct submission in two phases: bin-nadzor (reading from the mushaf) and bil-ghaib (submitting without the mushaf), which proved effective in improving reading accuracy and tajwid. The combination of both methods resulted in significant improvement, with 100% of students successfully memorizing the Qur'an in the fluent category (27 out of 27 students). The main supporting factors include the competence of teachers with sanad, a conducive environment, and students' internal motivation. This study offers an integrative model for the simultaneous implementation of halaqoh and musyafahah methods which has not been extensively studied in the context of Islamic boarding schools in the Tulang Bawang Barat region.